Cross-sectional TEM analysis of structural phase states in TiNi alloy treated by a low-energy high-current pulsed electron beam; Applied Surface Science; Vol. 327, № 1 - Neiman A. A.; Meisner L. L.; Lotkov A. I.; Koval N. N. Nikolay Nikolaevich; Semin V. O.; Teresov A. D. (2015, 2015)
Title screen